84 Does Dual-Task Gait Speed Predict Cognitive Performance in Midlife Type 2 Diabetes? Baseline Results from the ENBIND Study. (16th September 2019) - Dyer, Adam; Killane, Isabelle; Bourke, Nollaig; Woods, Conor; Gibney, James; O'Neill, Desmond; Reilly, Richard; Kennelly, Sean
Abstract: Background: Type 2 Diabetes (T2DM) in midlife is associated with a greater risk of dementia in later life. The longitudinal ENBIND Study is examining novel approaches to biomarker discovery in this high-risk group which may help identify those at greatest risk Methods: Non-demented participants with midlife T2DM (no micro/macrovascular complications) and matched controls were recruited. Following detailed health/diabetes assessment, general cognitive (MoCA) and computerised neuropsychological (CANTAB) assessment were performed. Gait was assessed by stopwatch and accelerometers across several tasks including self-selected and maximal gait speed in addition to a dual-task cognitive paradigm (reciting alternate letters of the alphabet). Bloods were analysed for C-Reactive Protein (CRP) and glycated haemoglobin (HbA1c). Between group differences were analysed using t-tests/non-parametric equivalents and linear regression used for multivariate analysis. Results: Sixty participants with T2DM (51.9 +/- 8.4 yrs) and 30 matched controls (52.3 +/- 7.9 yrs) were recruited. Controlling for demographic and cardiovascular covariates, T2DM was associated with a lower MoCA score, slower self-selected, maximal and dual-task gait speed (all p<0.05). Maximal gait speed (p =0.006) but not self-selected gait speed (p =0.47) was associated with poorer cognitive function. On multivariate analysis of the dual-task difference, both T2DM and lower MoCA score were associated with a poorer performance, (p<0.001, p= 0.003). Overall, performance in the lowest vs highest quartile on the dual-task gait paradigm was associated with a significantly poorer performance on the MoCA (p<0.001; median 27 vs 29). On multivariate analysis of laboratory parameters, higher CRP levels were associated with slower maximal (p =0.041) and dual-task (p=0.033) gait performance. Conclusion: Midlife T2DM is associated with poorer cognitive performance. Gait speed, and in particular dual-task gait speed, correlate strongly with general cognitive performance. Future work will tease out the specific domains of gait and cognition which are affected, and assess longitudinally in this high-risk group.